Business cycles and economic growth - Duesenberry, James S. (New York : McGraw-Hill, 1958)
The first part of the book is devoted to a detailed discussion of what determines investment and consumption.
oo 23/01/2019
Loans
Keywords: Business cycles; Saving and investment